Armeria villosa subsp. enritrianoi subsp. nov. (Plumbaginaceae) en el sureste de España (provincia de Jaén) - Blanca López, Gabriel; Cueto Romero, Miguel; Cueto Romero, Miguel; Fuentes Carretero, Julián; Fuentes Carretero, Julián; Tello Mora, Salvador; Tello Mora, Salvador (Acta Botanica Malacitana, 2018)
Nueva subespecie para el taxon Armeria villosa Girard.